Problem-Based Learning (PBL) in Grade V IPAS Under the Merdeka Curriculum at MI Terpadu Mutiara Assyifa, Bengkulu - Jumi Rostiana; Eka Puspa Dewi; Asmara Yumarni; Dini Widiyanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe the implementation of Problem-Based Learning (PBL) in Science and Social Studies (IPAS) for Grade V at MI Terpadu Mutiara Assyifa, Bengkulu City. Methodology: This research employed a qualitative descriptive method, with the Grade V teacher and students as data sources. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Findings: The results indicate that the planning and implementation of Problem-Based Learning (PBL) in Grade V IPAS at MI Terpadu Mutiara Assyifa have been effectively executed in accordance with the principles of the Merdeka Curriculum. The teacher developed teaching modules encompassing learning objectives, problem-based activity steps, and relevant assessments by incorporating contextual issues familiar to the students' lives. During implementation, PBL fostered active student engagement through discussion, investigation, and presentation. This approach had a positive impact on student understanding, enabling them to better relate the material to real-world situations and demonstrating improvements in critical thinking and communication skills. However, the application of PBL also faced several challenges, such as limited instructional time, varying student abilities, and restricted learning resources. Not all students participated optimally, particularly those with lower academic abilities who required more intensive guidance.